2012
DOI: 10.1136/heartjnl-2012-301799
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the underlying substrate in determining thrombus location in atrial fibrillation: implications for left atrial appendage closure

Abstract: The location of atrial thrombus in patients with AF is dependent on the underlying substrate. In valvular AF, more than half the thrombi are located in the left atrial cavity. In the non-valvular AF group, a smaller proportion of thrombi were located outside the appendage. However, in certain subgroups (ie. non anti-coagulated, left ventricular dysfunction or prior stroke) the chances of left atrial cavity thrombus are higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 56 publications
1
68
0
2
Order By: Relevance
“…Given the physiologic differences between an incompletely-closed versus a non-ligated LAA, it is possible that conventional stroke risk stratification schemes do not accurately predict the patient risk in the setting of such an entity. The same is for instance also true of patients with valvular (rheumatic) AF in whom the risk of stroke is nearly 17-fold greater, and virtually independent of the CHADS 2 /CHA 2 DS 2 -VASc risk score (2). As such, these findings support the notion that the presence of incomplete LAA closure may in fact be "worse" than no closure at all (7,13).…”
Section: Limitation Of Conventional Risk Stratification Scoressupporting
confidence: 76%
See 1 more Smart Citation
“…Given the physiologic differences between an incompletely-closed versus a non-ligated LAA, it is possible that conventional stroke risk stratification schemes do not accurately predict the patient risk in the setting of such an entity. The same is for instance also true of patients with valvular (rheumatic) AF in whom the risk of stroke is nearly 17-fold greater, and virtually independent of the CHADS 2 /CHA 2 DS 2 -VASc risk score (2). As such, these findings support the notion that the presence of incomplete LAA closure may in fact be "worse" than no closure at all (7,13).…”
Section: Limitation Of Conventional Risk Stratification Scoressupporting
confidence: 76%
“…In patients with non-valvular AF, the risk of ischemic stroke/systemic embolization is nearly 5-fold greater after adjusting for all other risk factors (1). The left atrial appendage (LAA) has been identified as a common site of thrombus formation in patients with AF (2). As such, the LAA has been targeted for surgical closure using a variety of techniques for over 6 decades, a practice that is frequently performed in conjunction with mitral valve and AF surgery (3,4).…”
mentioning
confidence: 99%
“…(20) Also to be considered, the LA cavity rather than the appendage can be the site of thrombus formation in more than half of patients with valvular AF and 1 in 9 with nonvalvular AF. (21) Endothelial dysfunction, systemic inflammatory response and atrial hypocontractility as cause and consequence of a fibrotic atrial cardiomyopathy have been implicated as the drivers of a hypercoagulable state in AF. (8) These factors do not abate in the absence of arrhythmia and advocate that AF, whether persistent or paroxysmal, could itself be viewed as a vascular disease ( Figure 1).…”
Section: Atrial Fibrillation As a Vascular Diseasementioning
confidence: 99%
“…However, transesophageal echocardiography guided cardioversion can be facilitated in the absence of left atrial and left atrial appendage thrombus. (14) In this instance, it is essential that effective peri--cardioversion anticoagulation is commenced and maintained for at least four weeks after to reduce new thrombus formation due to atrial stunning following restoration of sinus rhythm. (15,16) Importantly, the effect of atrial stunning is not limited to those who underwent electrical cardioversion with documented negative atrial inotropic effect seen in those treated with anti--arrhythmic drugs.…”
Section: Hemodynamically Stable Af With Onset >48 Hours or Unknowmentioning
confidence: 99%